Decannulation in Trisomy 21 patients undergoing laryngotracheal reconstruction. (January 2023) - Blumenthal, Daniel; Leonard, James A.; Habib, Andy; Behzadpour, Hengameh; Lawlor, Claire; Preciado, Diego
Abstract: Background: Down Syndrome (DS) patients are more susceptible to either congenital or acquired subglottic stenosis (SGS). This often creates a multilevel airway obstruction and can lead to tracheostomy dependence early in life. As a result, they may require Laryngotracheal Reconstruction (LTR) to achieve decannulation. The primary objective of this study was to assess decannulation rates, time to decannulation and potential barriers to decannulation in DS patients undergoing LTR. Methods: We performed a retrospective chart review from 2008 to 2021 of 193 children who underwent LTR for treatment for laryngotracheal stenosis at a stand-alone tertiary children's hospital. The relationship between clinical data and decannulation status was evaluated using multivariable logistic regression and Fisher exact tests. Time to decannulation analysis was performed using Kaplan Meier analysis and evaluated with log-rank and Cox proportional hazards regression. Results: We determined that DS patients carry an inherit risk for decannulation failure compared to the general population (OR: 6.112, P = . 044, CI 1.046–35.730). Of the 8 patients with DS only three were decannulated. Overall, patients with Trisomy 21 had a significantly increased time to decannulation when compared to all LTR patients (P = .008, Log-rank). We found that these patients are more likely to have both suprastomal collapse (P = .0004, Fischer's Exact) and Tracheomalacia (P = .034, Fischer's Exact) compared to all other LTR patients. While post-operative tracheomalacia did not significantly affect decannulation failure (P = .056, Fischer's Exact) it did significantly prolong decannulation in all LTR patients (P = .018, Log-rank). Conclusion: Trisomy 21 patients are at an increased risk for decannulation failure. Our study illustrates that these poor outcomes are likely a result of conditions more commonly found in this cohort including: narrow tracheal caliber, tracheomalacia and hypotonia. Highlights: Trisomy 21 patients are more likely to present with tracheomalacia. Tracheomalacia prolongs decannulation in laryngotracheal reconstruction patients. Multilevel collapse prolongs decannulation in Trisomy 21 patients. Trisomy 21 patients are at an increased risk for decannulation failure after laryngotracheal reconstruction.